PERLINDUNGAN DATA PRIBADI DITINJAU DARI TEORI PERLINDUNGAN HUKUM DAN TEORI PERLINDUNGAN HAK ATAS PRIVASI: Personal Data Protection Reviewed from Legal Protection Theory and Right to Privacy Protection Theory - Aruan, Jonathan Elkana Soritua (Jurnal Globalisasi Hukum., 2024)
The emergence of Corona-virus 19 (COVID-19) requires the Indonesian government to impose social distancing provisions in the form of laws and regulations so that the Indonesian government can reduce the percentage and rate of spread of COVID-19 in the country. As a result of the social distancing policy, people depend on information technology to support their activities. In using information technology services, technology service providers require technology service users to fill in personal data information and upload personal identity documents. Technology service providers ask for approval from users that the information and documents that have been provided will only be used for the benefit of technology services, will not be used for other things without the consent of technology service users. With regard to the protection of personal data, the Indonesian government issues regulations regarding the protection of personal data. However, recently there has been a leak of people's personal data that is misused by unauthorized parties. This is contrary to one of the obligations of the Indonesian government which must ensure the protection of people's personal data.